ANALISIS PENGARUH BRAND IMAGE, HARGA, DAN REVIEW PRODUCT TERHADAP KEPUTUSAN PEMBELIAN SKINCARE WARDAH PADA MAHASISWA UNAI - RICKA PUTRI YANI BR SINAGA; JOAN YULIANA HUTAPEA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
The trend of people's needs in skincare is getting higher. Beautiful and healthy facial skin is an important factor to support appearance. With the existence of beauty standards in society, everyone wants to have smooth, bright, and youthful-looking facial skin. The researcher aims to conduct research on whether brand image, price, product reviews have an effect on purchasing decisions for Wardah brand skincare products. The data collection technique was in the form of a questionnaire that used a Likert scale and was distributed online using google form and which answered 100 respondents who were students of the Indonesian Adventist University. The tests carried out for this research are validity, reliability, normality, multicollinearity, coefficient of determination, descriptive test, multiple linear regression analysis, t test, f test. From the partial test results, the price has an influence on purchasing decisions, a significant value of 0.000 and has a t count of 9,333 > 1,985, while the other two variables, namely brand image and product review, have no significant effect on purchasing decisions with the results of t count 0,476 < t table 1,985 and t count 0.300 < t table 1.985. From the results of the F -test research, the brand image, price and product review variables have a simultaneous influence on purchasing decisions with the results of F count 58.632 > F table 2.693.